Developing a Social Cognition Task for fMRI in Patients with Mild Traumatic Brain Injury - Reyes Gavilan, Pablo Alexander (2017)
Social cognition impairments are frequently found in patients with mild traumatic brain injury (TBI) when structural lesions may not reveal the severity of the injury. Though instruments used to assess social behavior are thought to be sensitive, the absence of structural damage in TBI patients may lead to underscore such problems. The aim of this study was to develop a complementary diagnostic tool such as a paradigm for functional Magnetic resonance Imaging (fMRI) involving a simple task that could tell how patients understand certain complex social behavior by identifying different movements with or without social intentions where language and complex cognitive process were not required. Eleven patients with mild TBI and social cognition difficulties and twelve control subjects were matched by demographic variables. A paradigm of social fMRI was developed by using dots in movement representing human motion, human motion with social intention such as dancing or sharing, and dots moving without meaning. Patients had less activation in parietotemporal junction and bilateral middle frontal gyrus in the social perception task movement compared with control group subjects. The fMRI paradigm developed can be an additional diagnostic tool for identifying social cognition impairments in mild TBI patients. Regardless the absence of structural injury, changes in activation areas suggest a prospective use of this tool since clinical, cognitive and functional outcomes support such finding.